Limitazioni alla libertà religiosa e principio di proporzionalità davanti alle Corti: una prospettiva comparata (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Introduzione - 2. “Breve durata” delle restrizioni e proporzio-nalità: l’interpretazione del Bundesverfassungsgericht - 3. Il Consiglio di Stato francese e la “question de proportionnalité” della libertà di culto - 4. “Secular gatherings” v. “secular businesses”: il tertium comparationis nella giurisprudenza della Corte Suprema statunitense - 5. Emergenza sanitaria e test di proporzionalità nella giurisprudenza di Strasburgo: brevi considerazioni de iure condendo - 6. Conclusioni.Restrictions on Religious Freedom and the Principle of Proportionalitybefore the Courts: A Comparative PerspectiveABSTRACT: The emergency legislation through which the legal systems have tried to cope with the Covid-19 pandemic has necessitated new forms of balancing health protection and other fundamental freedoms, including freedom of religion. The aim of this paper is to analyse the different ways in which the superior Courts have applied the principle of proportionality, with the purpose of trying to assess the extent to which the different sensitivity of judges (especially as regards the identification of the tertium comparationis) has affected the effective protection of freedom of religion during the pandemic. In particular, a comparison will be made among the statements of the Bundesverfassungsgericht, the Conseil d'État and the US Supreme Court, which have balanced the right to health and religious freedom. Short concluding remarks will be addressed to the possible role of Strasbourg jurisprudence in guiding the work of national judges dealing with the proportionality test, also in a post-pandemic perspective.